A meta-analysis of acute use of alcohol and the risk of suicide attempt. Issue 5 (8th December 2016) - Borges, G.; Bagge, C. L.; Cherpitel, C. J.; Conner, K. R.; Orozco, R.; Rossow, I.
Abstract : Background: No review has used a meta-analytic approach to estimate common odds ratios (ORs) for the effect of acute use of alcohol (AUA) on suicide attempts. We aim to report the results of the first meta-analysis of controlled epidemiological studies on AUA and suicide attempt. Method: The English-language literature on Medline, PsycINFO and Google Scholar was searched for original articles and critical review on AUA and suicide attempt (period 1996–2015). Studies had to report an OR estimate for this association. Common ORs and 95% confidence intervals (CIs) from random effects in meta-analyses for any AUA and two levels of alcohol use on suicide attempt were calculated. Results: In all, seven studies provided OR estimates for the likelihood of suicide attempt by AUA, compared with those who did not drink alcohol. Studies used case–control ( n 3) and case–crossover designs ( n 4). Meta-analysis revealed a common OR of 6.97 (95% CI 4.77–10.17) for any AUA. Using four studies, 'low levels of acute drinking' resulted in an OR of 2.71 (95% CI 1.56–4.71) and 'high levels' had an OR of 37.18 (95% CI 17.38–79.53). Conclusions: AUA is associated with increased likelihood of a suicide attempt, particularly at high doses. Such data should be incorporated into estimates of the burden of disease associated with alcohol use, which are currently limited by a consideration of only alcohol's chronic effects. Future research should focus on the mechanisms through which AUA confers risk for attempt.